A Novel Dopamine Transporter Inhibitor CE-123 Improves Cognitive Flexibility and Maintains Impulsivity in Healthy Male Rats - Nikiforuk, Agnieszka; Kalaba, Predrag; Ilic, Marija; Korz, Volker; Dragačević, Vladimir; Wackerlig, Judith; Langer, Thierry; Höger, Harald; Golebiowska, Joanna; Popik, Piotr; Lubec, Gert (Frontiers in Behavioral Neuroscience, 2017)
Reduced cognitive abilities are often characterized by an impairment of flexibility, i.e. the ability to switch from learned rules or categories that were important in certain contexts to different new modalities that rule the task. Drugs targeting the dopamine transporter (DAT) are widely used for their potential to enhance cognitive abilities. However commercially available drugs are of limited specificity for DAT, blocking also noradrenaline and serotonine transporters, that can lead to unwanted side effects in healthy subjects. Therefore, we tested a newly synthetized compound (CE-123) with higher specificity for DAT in male rats in an attentional set-shifting task (ASST), that proves for cognitive flexibility and a 5-choice serial-reaction time task (5-CSRTT) assessing visuospatial attention and impulsivity. Treated rats at a dose of 0.3 and 1.0 but not 0.1 mg/kg bodyweight showed reduced extradimensional shifts in the ASST compared to controls indicating increased cognitive flexibility. Rats treated with R-Modafinil, a commercially available DAT inhibitor at a dose of 10 mg/kg bodyweight showed increased premature responses, an indicator of increased impulsivity, during a 10s but not a 2.5 s, 5 s or 7.5 s intertrial interval when compared to vehicle treated rats in the 5-CSRTT. This was not found in rats treated with CE-123 at the same dose as for R-Modafinil. Visuospatial attention, except premature responses, did not differ between R-Modafinil and CE-123 treated rats and their respective controls. Thus, CE-123 increased cognitive flexibility with diminished impulsivity.